Acute seizure suppression by transcranial direct current stimulation in rats. Issue 8 (3rd July 2015) - Dhamne, Sameer C.; Ekstein, Dana; Zhuo, Zhihong; Gersner, Roman; Zurakowski, David; Loddenkemper, Tobias; Pascual‐Leone, Alvaro; Jensen, Frances E.; Rotenberg, Alexander
Abstract Objective Cathodal transcranial direct current stimulation (tDCS) is a focal neuromodulation technique that suppresses cortical excitability by low‐amplitude constant electrical current, and may have an antiepileptic effect. Yet, tDCS has not been tested in status epilepticus (SE). Furthermore, a combined tDCS and pharmacotherapy antiseizure approach is unexplored. We therefore examined in the rat pentylenetetrazol (PTZ) SE model whether cathodal tDCS (1) suppresses seizures, (2) augments lorazepam (LZP) efficacy, and (3) enhances GABAergic cortical inhibition. Methods Experiment 1 aimed to identify an effective cathodal tDCS intensity. Rats received intraperitoneal PTZ followed by tDCS (sham, cathodal 1 mA, or cathodal 0.1 mA; for 20 min), and then a second PTZ challenge. In Experiment 2, two additional animal groups received a subtherapeutic LZP dose after PTZ, and then verum or sham tDCS. Clinical and electroencephalography (EEG) epileptic activity were compared between all groups. In Experiment 3, we measured GABA‐mediated paired‐pulse inhibition of the motor evoked potential by paired‐pulse transcranial magnetic stimulation (ppTMS) in rats that received PTZ or saline, and either verum or sham tDCS. Results Cathodal 1 mA tDCS (1) reduced EEG spike bursts, and suppressed clinical seizures after the second PTZ challenge, (2) in combination with LZP was more effective in seizure suppression and improved the clinical seizure outcomes compared to either tDCS or LZP alone, and (3) prevented the loss of ppTMS motor cortex inhibition that accompanied PTZ injection. Interpretation These results suggest that cathodal 1 mA tDCS alone and in combination with LZP can suppress seizures by augmenting GABAergic cortical inhibition.